Antecedents of outsourcing decision among service industry in Sabah - Liew, Li Ling (2008)
Outsourcing was defined as a method of new management thinking that allowed external parties to perform some of the organization's business functions which were used to perform internally before. When making the outsourcing decision, organizations had to consider the factors of demographic like age, size, and location of organizations, strategic factors like cost efficiency, risk management and core competencies enhancement and environmental factor like economic condition because they were main drivers in influencing the outsourcing decision. From the seven hypotheses that tested, four of the hypotheses were significant, where the independent variables were age of organizations, size of organizations, location of organizations, and cost efficiency. It meant that all these four independent variables had an impact/relationship on outsourcing decision, while the other independent variables like risk management, core competencies enhancement and economic condition had no impact toward outsourcing decision.